Generational Diversity of Employees and the Preferred Organizational Culture Model - Wziątek-Staśko, Anna Lucyna (Acta Universitatis Lodziensis. Folia Oeconomica, 2019)
The convergence of key values for an organization with values relevant to employees is a research problem of high priority for modern entrepreneurs and one of the key challenges that they should devote special attention to. The subject of considerations taken in this article is the organizational culture and its perception by employees of different ages. The increasingly visible stereotyping of features and preferences of representatives of different generations, regarding their functioning in the work environment, has become an inspiration to undertake original research in this area. The participants of the research were 664 Polish respondents. The quantitative methods were used in the research process. The purpose of the article is to present the current and desired organizational culture model in the assessment of employees at different ages.